2023
DOI: 10.3390/healthcare11070938
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Photobiomodulation Therapy in the Treatment of Pain and Inflammation: A Literature Review

Abstract: The main objective of this literature review was to analyze the efficacy of (PBM) therapy application on subjects with chronic pain and inflammation, and furthermore, to evaluate the methodological quality of the collected literature. The search was conducted using five databases: PubMed, ProQuest, Scopus, Web of Science, and PEDro. The keywords “low level laser therapy”, “chronic pain”, and “inflammation” provided the selection of RCTs that were published within the last 5 years, conducted in humans, and writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Photobiomodulation (PBM) is a non-invasive therapy that entails the use of red to infrared (IR) light (wavelengths of 600 to 1100 nm) to stimulate cellular processes that promote tissue healing and regeneration [ 1 3 ]. Additionally to being studied and used as a therapy for pain relief [ 4 , 5 ], wound healing and skin rejuvenation [ 6 , 7 ], the neuromodulation effects of PBM, when applied to the scalp, have been increasingly more studied, with several clinical studies showing that it could be a safe, non-invasive, and non-destructive alternative to conventional treatments for various neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Photobiomodulation (PBM) is a non-invasive therapy that entails the use of red to infrared (IR) light (wavelengths of 600 to 1100 nm) to stimulate cellular processes that promote tissue healing and regeneration [ 1 3 ]. Additionally to being studied and used as a therapy for pain relief [ 4 , 5 ], wound healing and skin rejuvenation [ 6 , 7 ], the neuromodulation effects of PBM, when applied to the scalp, have been increasingly more studied, with several clinical studies showing that it could be a safe, non-invasive, and non-destructive alternative to conventional treatments for various neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism is not fully understood [2][3][4][5]21,22], previous studies using electrophysiological techniques have shown that PBM affects the activity of paintransmitting nerves [23][24][25][26][27][28][29]. These include a few studies in which neural activity was recorded in the spinal dorsal horn, the entry point for pain signals in the central nervous system [30], but these studies do not mention the Rexed laminae of the spinal dorsal horn [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Low-power light-emitting diodes (LEDs) and lasers are devices that emitted radiations with clinical applications, such as pain relief, wound healing, treatment of acne and anti-inflammatory activity based on the photobiomodulation (PBM) process [1][2][3][4]. Lasers are able to emit monochromatic, * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%